Education, entrepreneurship and economic growth: evidence from Malaysia / Sarah Fahani Mohd Fadhil and Mohd Rafi Yaacob - Mohd Fadhil, Sarah Fahani; Yaacob, Mohd Rafi (2010)
Economists have long stressed the importance of human capital to the process of growth. Low human capital investment and poor schooling outcomes lead households into poverty trap. Previous research saying that entrepreneurship is able to raise the economy and alleviate the poverty level. In order to achieve the targeted economy level, which is to be a full industrial country; the future of a country depends on the quality of entrepreneurs. Developing countries are aware of this issue and therefore, they improve their policy to strengthen their education systems by providing human capital stock by which directly or indirectly produce educated entrepreneurs. Against the background the purpose of this paper is to explore the issues related to education, entrepreneurship and economic growth in the context of Malaysia. This research capitalises the Solow model augmented human capital in an effort to explain variations in growth levels. Measurement of human capital stock between year 1980 and 2007 has been constructed and employed in growth accounting exercises. This paper gives special attention to the total of enrolment at primary, secondary and tertiary level of education and its affect to economic growth. In addition logistic and linear regressions are used to analyze the correlation between educations and economic growth. The results of this study shows that education is positively and significantly impact the economic growth. The result of the study is instructive, A high priority should be given to human capital accumulation and productivity growth, if Malaysia to sustain its growth and welfare improvement in the next decade.